2018
DOI: 10.1051/0004-6361/201732041
|View full text |Cite
|
Sign up to set email alerts
|

Strong non-radial propagation of energetic electrons in solar corona

Abstract: Analyzing the sequence of solar energetic electron events measured at both STEREO-A (STA) and STEREO-B (STB) spacecraft during 17–21 July 2014, when their orbital separation was 34°, we found evidence of a strong non-radial electron propagation in the solar corona below the solar wind source surface. The impulsive electron events were associated with recurrent flare and jet (hereafter flare/jet) activity at the border of an isolated coronal hole situated close to the solar equator. We have focused our study on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…As this effect is not observed in the event under study, we believe that the accuracy of the radio triangulation results is within the limits induced by the method itself. Further, the same propagation path of the subsequent type III bursts was already reported in some other studies (Reiner et al 2009;Klassen et al 2018;Zhang et al 2019). We think that the scattering, that can be strongly event dependent (Aurass et al 1994;Zlotnik et al 1998), is probably not a dominant process in this event.…”
Section: Propagation Of the Radio Emissionsupporting
confidence: 81%
“…As this effect is not observed in the event under study, we believe that the accuracy of the radio triangulation results is within the limits induced by the method itself. Further, the same propagation path of the subsequent type III bursts was already reported in some other studies (Reiner et al 2009;Klassen et al 2018;Zhang et al 2019). We think that the scattering, that can be strongly event dependent (Aurass et al 1994;Zlotnik et al 1998), is probably not a dominant process in this event.…”
Section: Propagation Of the Radio Emissionsupporting
confidence: 81%
“…Recently, an SEP study by Klassen et al (2018) reported an electron event observed by STEREO at 1 au with an impulsive rise and strong anisotropy, clearly indicating a good magnetic connection between the flare site and the observer, despite the fact that the source was 90 • east of the nominal magnetic footpoint. As was the case for the event we discuss, Klassen et al (2018) found that PFSS modeling did not account for the magnetic connection in the event they studied, at least in part because their event was also over the limb as seen from Earth. EUV observations showed a very long jet propagating from the AR to the nominal magnetic footpoint of the observer, highly inclined from the radial direction.…”
Section: Discussionmentioning
confidence: 99%
“…Expansion of the AR field lines between the photosphere and corona by this amount is not impossible, but a survey of 14 yr of PFSS maps suggests it would likely require a region of open field lines in the photosphere at least ∼5 • in diameter (see Figure 4 of Wiedenbeck et al (2013)). However, as the Klassen et al (2018) observations show, at times the PFSS model may simply fail to correctly identify existing highly non-radial field lines near ARs. Alternatively, drift along the nearby HCS (Battarbee et al 2018) may also have played a role.…”
Section: Discussionmentioning
confidence: 99%
“…Various scenarios have been proposed Article number, page 1 of 12 arXiv:1903.09072v1 [physics.space-ph] 21 Mar 2019 to explain these observations, ranging from processes occurring in the corona, such as strongly tilted non-radial magnetic fields (e.g. Klein et al 2008;Klassen et al 2018) or asymmetric coronal shocks waves (e.g. Lario et al 2014), to processes occurring in the interplanetary medium such as meandering field lines and/or different pitch-angle scattering conditions along particle paths residing in different solar wind streams (e.g.…”
Section: Introductionmentioning
confidence: 99%